Selecting sustainable building materials using system dynamics and ant colony optimization - Marzouk, Mohamed; Abdelhamid, Manal; Elsheikh, Mohamed (Journal of Environmental Engineering and Landscape Management, 2013)
Selecting environmentally preferable building materials is one way to reduce the negative environmental impacts associated with the built environment. This paper proposes a framework that incorporates environmental and economic constraints while maximizing the number of credits reached under the Leadership in Energy and Environmental Design (LEED) rating system. The framework helps decision makers with the appropriate selection of conventional and green building materials. It consists of two modules: System Dynamics module and Ant Colony Optimization module. The paper describes the developments made in these two modules, where the selection of building materials is carried out based on LEED credits and costs. The proposed framework provides more credits when using environmentally friendly materials. A case study of residential building is presented to demonstrate the main features of proposed framework.